Engineering design methods : strategies for product design - Cross, Nigel, 1942- (Chichester ; New York : John Wiley and Sons, 1994)
This book is about: The nature of design; The design process; Design methods; Clarifying objectives; Establishing functions; ...
Keywords: Engineering design; Engineering design